Iodine Materials Interaction Database - Zschätzsch, Daniel; Justus Liebig University Giessen (My University, 2021)
A database of the reaction of iodine with various materials. Iodine treatments: atmospheric, sputter, and plasma treatment.
Keywords: Iodine; Satellite; Materials; Plasma; Sputter-effects; Atmosphere; ddc:530